Silent Yet Social: Studi Preferensi Komunikasi Generasi Z di Media Sosial - Nurijadi, Bintang; irawan, Novida (Jurnal Mahardika Adiwidia, 2025)
This study aims to understand Gen Z's digital non-verbal communication preferences through a literature study approach. The theoretical framework used includes symbolic communication theory, media richness theory, and the concept of digital native. The method used is a systematic literature study of scientific journals and books published in the last five years. The findings show that Gen Z is more comfortable expressing themselves through digital non-verbal communication due to digital socio-cultural factors, the need for speed of communication, and psychological comfort in conveying messages indirectly. The results of the study also revealed that although the use of digital symbols increases expressivity, it also has the potential to reduce the depth of emotion in interpersonal communication and trigger challenges in cross-generational and professional communication. In conclusion, digital non-verbal communication has become an integral part of Gen Z's interaction patterns, which requires adaptation from various parties, including educational institutions and the world of work. This study contributes to the development of digital communication theory and offers practical implications for more inclusive communication in the digital era.